(untitled) (Research, Society and Development, 2020)
In recent years the forest sector has suffered losses caused by exotic pests, especially those related to Eucalyptus culture. The present study aimed to assess the compatibility of some insecticides used in the management of shell psilidio, bronze bug and gall wasp that attack eucalyptus with the fungus Beauveria bassiana. For both used the Acephate Insecticide, Imidacloprid and Acetamiprid on average dose recommended in the package leaflet, and B. bassiana (PL 63 strain). All tests were performed in vitro by evaluating parameters related to vegetative growth and germination of conidia, besides compatibility or not between the fungus and insecticides through the IB (biological index). Imidacloprid provided higher vegetative growth while the witness Acephate showed no difference from the same. In conidia production Acephate gave values greater than witness while others have significantly reduced this parameter. Not found effect of treatments on the germination of conidia of B. bassiana. Evaluating the parameters together through IB, it was found that Acephate and imidacloprid were compatible with B. bassiana as Acetamiprid was toxic.